Keep it simple: Central bank communication and asset prices - Haroon Mumtaz; Jumana Saleheen; Roxane Spitznagel (Queen Mary University of London, School of Economics and Finance, 2023)
This paper studies the impact of different types and styles of Bank of England Monetary Policy Committee (MPC) communication on asset prices (stock prices, gilt yields and interest rate futures) from 1999-2023. We extend MPC communication to include MPC speeches and find MPC speeches to be an important driver of asset prices. We also show that complex and ambiguous communication leads to greater asset price volatility than simple and clear communication. Central banks that want to avoid generating volatility in financial markets should keep it simple. Our results suggest that by ignoring the type and style of monetary policy communication, the previous literature has disregarded an important source of variation in asset prices.
Keywords: E52; E58; G12; 330; Monetary policy; central bank communication; high-frequency data